2021
DOI: 10.1177/09673911211040360
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of castor oil–based polyurethane foams for oil sorption S10 and S500: Influence of porous size and statistical analysis

Abstract: This study evaluates the efficiency of castor oil–based polyurethane foams for oil sorption S10 and S500, focusing on the influence of the pores’ size. Different foams were produced by varying the polyol: isocyanate ratio (1:0.3; 1:0.5; 1:1.0; 1:1.5; and 1:2.0). The physicochemical properties, morphology, density, and Hg porosity were determined. The sorption capacity was influenced by exposure time, oil viscosity, and concentration of the reagents, considering variations in the hydrophobicity, void content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 61 publications
2
16
0
Order By: Relevance
“…Castor oil is attractive to obtain PUR because it has a high number of hydroxyl groups (OH) that react with isocyanate (NCO) to form urethane bonds 15 . These hydroxyl groups are derived from ricinoleic acid, which constitutes approximately 80% of the oil.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Castor oil is attractive to obtain PUR because it has a high number of hydroxyl groups (OH) that react with isocyanate (NCO) to form urethane bonds 15 . These hydroxyl groups are derived from ricinoleic acid, which constitutes approximately 80% of the oil.…”
Section: Introductionmentioning
confidence: 99%
“…These hydroxyl groups are derived from ricinoleic acid, which constitutes approximately 80% of the oil. The hydrophobic nature of the triglycerides in castor oil contributes to its excellent mechanical properties, such as the high tensile strength 15–17 . Castor oil‐based polyurethanes are characterized by hard regions (where polymeric chains are oriented) and soft regions (where the chains are random) 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various vegetable oils, such as palm oil [ 44 ], sunflower oil [ 45 ], rapeseed oil [ 46 ], castor oil [ 47 ] and canola oils [ 48 ] can be used to synthesize PU foams. The triglycerides of castor oil, rich in oleic acid (90%) with a combination of hydroxyl and unsaturated multi-functionality in the fatty acid chains, can react with isocyanates to form urethane linkages, i.e., interpenetrating polymer networks in PU foams [ 49 , 50 , 51 ]. The use of castor oil for oil adsorption application has been reported by modifying the surface with liquefied lignin-based PU foams.…”
Section: Introductionmentioning
confidence: 99%
“…The use of castor oil for oil adsorption application has been reported by modifying the surface with liquefied lignin-based PU foams. A study by Alves [ 50 ] et al reported a method for preparing castor oil-based PU foams with different polyol: isocyanate concentrations for diesel oil sorption. The use of açaí seeds [ 52 ] as an ecosorbent filler in castor oil-based PU and its applications in oil/water separators in grease traps in households and restaurants was demonstrated.…”
Section: Introductionmentioning
confidence: 99%